Polybenzimidazole-based polymeric ionic liquids (PILs): effects of `substitution asymmetry' on CO2 permeation properties - Shaligram, Sayali V.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric Ionic Liquids (PILs) are being considered as promising membrane materials for CO2 separation. Present work aims at investigating effects substitution asymmetry on imidazole moiety of two structurally different polybenzimidazoles (PBI-BuI and PBI-HFA) on physical, gas sorption and transport properties of the resulting film forming PILs possessing symmetric substitution, while keeping one of the N-substituent as methyl group. PILs were obtained with high degree of substitution. The halide anion of these PILs was exchanged with BF4-, Tf-2(N) over bar and HF (B) over bar anions. Effects of substituents, cationic backbone and type of anions on gas permeation properties of PILs using pure gases (He, H-2, N-2 and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. Combination of typical ionic liquid character (effective towards enhancing CO2 sorption) and looser chain packing (ease in gas diffusion) offered improved CO2 permeation characteristics. As an outcome, some of the PILs exhibited higher CO2 permeation than that of hydrogen, typically known as `reverse selectivity'. These asymmetrically substituted PILs enhanced not only the gas permeability, but also selectivity than their symmetrically substituted counterparts. (C) 2015 Elsevier B.V. All rights reserved.

Polybenzimidazole based polymeric ionic liquids possessing partial ionic character: effects of anion exchange on their gas permeation properties - Rewar, Anita S.; Shaligram, Sayali V.; Kharul, Ulhas K. (Journal of Membrane Science, 2016)
Polymeric ionic liquids (PILs) are emerging as promising membrane materials for CO2 separation. Present work is in continuation with our earlier efforts on evaluating gas permeation properties (especially, CO2) of film forming PILs based on polybenzimidazoles and efforts towards improving their permeability by structural tuning. This work specifically aims at evaluating effect of anion variation in chosen PILs possessing partial N-quaternization of imidazole moiety of PBI-Bul. Three anions (viz., Tf2N-, BF4- and Ac-) were chosen for the bromide exchange of two PILs, viz., [TBzPBI-Bul][Br](10) and [TBzPBI-Bul][Br](18), possessing degree of PEI N-quaternization (DQ) as 10 and 18%, respectively. Concurrent effects of variation in anion and DQ were analyzed in terms of physical and gas permeation properties of the resulting PILs. All of them possessed amorphous nature, adequate thermal stability ( >= 250 degrees C) and solvent solubility, which are primary requisites towards their applicability as a membrane material. PILs possessing BF4- anion exhibited improved CO2 permeability coefficient as well as its permselectivity over CH4 and N-2, in comparison to their counterparts with other anions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; Gas separation; Polybenzimidazole; Polymeric ionic liquids (PILs)